Factors influence whistleblowing / Siti Nur Atikah Che Man @ Othman - Che Man @ Othman, Siti Nur Atikah
Whistleblowing practice is one of the issue related with employees. This research study has been conducted to examine factors that influencing whistleblowing practice. The independent variable that include in this research study are job satisfaction, level of moral reasoning, employee organizational structure, attitudes toward whistleblowing and perceived behavioral control. Researcher want to identify whether the independent variables related effect the whistleblowing practice. The result revealed that level of moral reasoning, employee organizational structure and attitudes toward whistleblowing are positively and significant with whistleblowing. Meanwhile, job satisfaction and attitude toward whistleblowing negatively and significant with whistleblowing practice. The 322 set of questionnaire have been prepared and distributed through google form to the respondent who are related to this research study such as employees who are working in Institut Perubatan Dan Pergigian Termaju, Universiti Sains Malaysia, Pulau Pinang. Further, Statistical Package for the Social Sciences (SPSS) version 23 also have been used to calculate the data from the questionnaire.